Study of the Performance of Paraffin Wax as a Phase Change Material in Packed Bed Thermal Energy Storage System - Naeem, Lubna A.; Al-Hattab, Tahseen A.; Abdulwahab, Majid I. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The present work deals with an experimental investigation of charging and discharging processes in thermal storage system using a phase change material PCM. Paraffin wax was used as the PCM which is formed in spherical capsules and packed in a cylindrical packed column which acted as an energy storage system. Air was used as the heat transfer fluid HTF in thermal storage unit. The effect of flow rate and inlet temperature of HTF on the time of charging and discharging process were studied. The results showed that the faster storage of thermal energy can be made by high flow rate of heat transfer fluid HTF and high inlet temperature of heat transfer fluid. It was found that at 65°C HTF inlet temperature, the melting and solidification processes accelerated by 27.9% and 57.14% respectively, when the flow rate was increased from 9 to 24 L/s. Also, when the HTF inlet temperature changed from 65°C to 80°C, the time needed to complete melting process decreased by 38.8%.